2019
DOI: 10.3389/fpsyt.2019.00305
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the “Semente” Program on the Family-Focused Practice of Mental Health Professionals in Portugal

Abstract: Background: Children of parents with mental illness (COPMI) are a high-risk group. There is a strong association between parents’ psychiatric disorders and the incidence of psychopathology in their children. These children need to be identified and supported by mental health workers early, and hence, clinical practice in adult mental health services needs to change from a focus on individual patients to a more systemic family focus. “Semente,” a mental health promotion program developed by the Psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 47 publications
1
19
0
2
Order By: Relevance
“…These constraints may include lack of motivation, heavy workload, no opportunities to receive supervision, and lack of support from colleagues and institutions [ 36 ]. In Portugal, one study evaluated the effectiveness of a training program on FFP and found that, although the training program could effectively increase mental health workers’ knowledge and skills on FFP, it did not promote workers’ actual support to carers and children in their clinical work [ 31 ]. Therefore, in order to enhance family-focused mental health services, multilevel strategies are needed to address various factors that may impede the effective implementation of family-focused services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These constraints may include lack of motivation, heavy workload, no opportunities to receive supervision, and lack of support from colleagues and institutions [ 36 ]. In Portugal, one study evaluated the effectiveness of a training program on FFP and found that, although the training program could effectively increase mental health workers’ knowledge and skills on FFP, it did not promote workers’ actual support to carers and children in their clinical work [ 31 ]. Therefore, in order to enhance family-focused mental health services, multilevel strategies are needed to address various factors that may impede the effective implementation of family-focused services.…”
Section: Discussionmentioning
confidence: 99%
“…Higher subscale scores represent more positive appraisals of the corresponding aspects of FFP (e.g., a higher subscale score on “family-focused policy and procedure” represents a more positive appraisal of family-focused policy and procedure in the workplace). The FFMHPQ has sound validity and reliability [ 28 ] and has been used with different profession types [ 27 ], in different health care settings [ 30 ], and in different cultures [ 14 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Norway, one initiative involved a two‐stage clinical process: First, templates were used to ensure child identification at assessment, followed by the offer to parents of ‘Child Talks’, a short intervention focused on child resilience and information provision (Lauritzen, Reedtz, Van Doesum, & Martinussen, 2014). This was mirrored in Portugal where increased acknowledgement of the children of psychiatric patients following the implementation of practitioner training was coupled with organizational change (Doesum et al., 2019). It should be noted that transforming service provision is effortful and sustaining innovation generates ongoing challenges (Greenhalgh & Papoutsi, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Van Doesum et al. ( 2019 ) berichten von einer Zunahme von Wissen und Fertigkeiten über familienorientierte Praxis bei Fachkräften der Erwachsenen- sowie der Kinder- und Jugendpsychiatrischen Klinik durch ein Training in familienorientierter Kurzintervention in der Klinikroutine. Das Training bestand aus einer Vorlesung, Rollenspielen sowie Diskussionen zu Hürden und Lösungen einer erfolgreichen Implementierung.…”
Section: Implementierungsstudie „Einstellungen Wissen Und Fertigkeiten Der Fachkräfte“ Im Chimps-net-konsortiumunclassified